Renal related disorders in concomitant Schistosoma haematobium-Plasmodium falciparum infection among children in a rural community of Nigeria - Olajumoke A. Morenikeji; Ituna E. Eleng; Omotayo S. Atanda; Oyetunde T. Oyeyemi (Elsevier, 2016)
Summary: Schistosomiasis and malaria are two common parasitic diseases that are co-endemic in resource-poor communities of sub-Saharan Africa. This study aims to assess the effects of single and concomitant Plasmodium falciparum and Schistosoma haematobium infections on two indicators of renal injury in school children in a rural community of Nigeria. A cross-sectional epidemiological survey was carried out on a total of 173 schoolchildren between ages 6 and 18 years (mean age 11.4 ± 2.6 years). Urine and blood samples were collected by standard methods for concurrent microscopic diagnosis of S. haematobium and P. falciparum infections. Urinary blood (hematuria) and protein were determined using a urinalysis dipstick. The prevalence of single infections was 75.1% and 78.2% for S. haematobium and P. falciparum, respectively. A total of 57.1% individuals were infected with the two parasites. The prevalence of hematuria was significantly higher in the co-infection status (63.8%) than in single S. haematobium (52.2%) and P. falciparum (43.7%) infection statuses (p = 0.04), while no significant variation was recorded in proteinuria in the three infection statuses (p = 0.53). The proportion of children with renal injury associated with the co-infection of these parasites is very high, particularly in young children, who seem to have a higher prevalence of hematuria. Keywords: Schistosoma haematobium, Plasmodium falciparum, Concomitant infection, Abnormal urinary blood, Proteinuria